2022
DOI: 10.1111/imm.13520
|View full text |Cite
|
Sign up to set email alerts
|

Human FOXP3 and tumour microenvironment

Abstract: The tumour microenvironment (TME) is a complex system composed of cancer cells, stromal cells and immune cells. Regulatory T cells (Tregs) in the TME impede immune surveillance of tumours and suppress antitumor immune responses. Transcription factor forkhead box protein 3 (FOXP3) is the main marker of Tregs, which dominates the function of Tregs. FOXP3 was originally thought to be a Tregs-specific expression molecule, and recent studies have found that FOXP3 is expressed in a variety of tumours with inconsiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 77 publications
3
30
0
Order By: Relevance
“…A previous study found SLFN5 co-localization with T cells and M2-type macrophages in precancerous lesions of GC, implying that SLFN5 plays an immunosuppressive role in GC (23). Consistently, we found that SLFN5 is primarily expressed in Treg and naïve T cells, which play a tumor-promoting role in cancer (47). Similarly, high SLFN11 expression in breast cancer is related to more aggressive and immune-activated tumors, whereas low SLFN11 expression is associated with low aggressiveness and low immune activation status (48).…”
Section: Discussionsupporting
confidence: 75%
“…A previous study found SLFN5 co-localization with T cells and M2-type macrophages in precancerous lesions of GC, implying that SLFN5 plays an immunosuppressive role in GC (23). Consistently, we found that SLFN5 is primarily expressed in Treg and naïve T cells, which play a tumor-promoting role in cancer (47). Similarly, high SLFN11 expression in breast cancer is related to more aggressive and immune-activated tumors, whereas low SLFN11 expression is associated with low aggressiveness and low immune activation status (48).…”
Section: Discussionsupporting
confidence: 75%
“…FoxP3 regulatory T cells are an immunosuppressive subpopulation of CD4+ T cells that modulate the anti-tumor response mediated by CD8+ T cells. In the TIME, high levels of Tregs are frequently presented and their main effect is to create and maintain an immune tolerant environment [ 69 ]. 15 studies measured Tregs using the FoxP3 marker (46.8%) [ 28 31 , 35 , 37 , 42 , 58 , 59 , 64 67 , 70 , 71 ].…”
Section: Macrophagesmentioning
confidence: 99%
“…The upstream regulatory genes, the related signaling pathways, and the epigenetic changes of FOXP3 in tumors have not been fully elucidated. Meanwhile, both FOXP3 + Tregs and tumor-derived FOXP3 are expressed in TME [ 72 ], due to the complexity between the cross-talk of FOXP3 + Tregs and FOXP3 + tumor cells, and it is necessary to further study the performance of communication mechanisms and their effect on tumor biological behaviors.…”
Section: Limitations and Deficienciesmentioning
confidence: 99%